Farmer field school: Non-formal education to enhance livelihoods of Indonesian farmer communities. Issue 2 (15th March 2021) - Mariyono, Joko; Waskito, Jaka; Suwandi,; Tabrani,; Kuntariningsih, Apri; Latifah, Evy; Suswati, Enny
ABSTRACT: The Indonesian agricultural sector provides a high proportion of employment for the rural community. However, the farmers' livelihood is relatively low. Sending the farmers to non-formal education will enhance the livelihood of the community. In this study, we analyze the impact of farmer field school on Indonesia's rural community livelihoods. Data were collected using a participatory approach from 270 farmer groups that completed farmer field school in Sumatra, Java, and Bali. The results show that the farmer field school generated positive impacts on five capitals. Farmers realized the benefits of participating in the field school. They could increase farming efficiency by applying technology innovations, knowledge, and skills obtained from the field school. Farmer livelihoods in the community have been substantially enhanced.